Gamified Learning Unleashed: Mastering British Accents with Nearpod - Ahada, Ichi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Finding out if gamification affects students' Listening comprehension at the early university level is the goal of this study. With a quantitative research design, this study employs a quasi-experimental method. In total, 34 students were chosen by the researcher to participate in the experiment. Three meetings were used for pre- and post-tests by the researchers while gathering data. In experiment classes, the average pre-test and post-test scores are 0,62 and 4,67. From the statistical test, discovered Asymp.Sig (2-tailed)= 0,000 < 0,05 so Ha accepted and Ho rejected mean that there is the difference of result of studies before and after using nearpod gamification for listening to British accent. Researcher can therefore conclude that the listening students at Mulawarman English Education are significantly impacted by the use of Nearpod gamification in the learning process